Combustion characteristics of hydrogen in a noble gas compression ignition engine. (November 2021) - Taib, Norhidayah Mat; Mansor, Mohd Radzi Abu; Wan Mahmood, Wan Mohd Faizal
Abstract: Hydrogen eliminates carbon emissions from compression ignition (CI) engines, while noble gases eliminate nitrogen oxide (NO x ) emissions by replacing nitrogen. Noble gases can increase the in-cylinder temperature during the compression stroke due to their high specific heat ratio. This paper aims to find the optimum parameters for hydrogen combustion in an argon–oxygen atmosphere and to study hydrogen combustion in all noble gases, providing hydrogen combustion data with suitable engine parameters to predict hydrogen ignitability under different conditions. Simulations are performed with Converge CFD software based on the Yanmar NF19SK direct injection CI (DICI) engine parameters. The results are validated with the experimental results of hydrogen combustion in an argon–oxygen atmosphere with a rapid compression expansion machine (RCEM), and modifications of the hydrogen injection timing and initial temperature are proposed. Hydrogen ignition in an argon atmosphere is dependent on a minimum initial temperature of 340 K, but the combustion is slightly unstable. Helium and neon are found to be suitable for hydrogen combustion in low compression ratio (CR) engines. However, krypton and xenon require temperature modification and a high CR for stable ignition. Detailed parameter recommendations are needed to improve hydrogen ignitability in conventional diesel engines with the least engine modification.